2020
DOI: 10.1161/circoutcomes.119.006245
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Replacement in Low-Population Density Areas

Abstract: Background: Restricting transcatheter aortic valve replacement (TAVR) to centers based on volume thresholds alone can potentially create unintended disparities in healthcare access. We aimed to compare the influence of population density in state of Florida in regard to access to TAVR, TAVR utilization rates, and in-hospital mortality. Methods and Results: From 2011 to 2016, we used data from the Agency for Health Care Administration to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…We also found significant variability in the TAVR operator density and mean procedural volume by state‐ these findings are in support of prior studies demonstrating extensive geographic variation in the rates of TAVR utilization among the general population 9,10 . Geographic barriers are a single but important variable in an otherwise complex construct affecting access to TAVR care including socioeconomic status, ethnicity, race, and insurance status, which combined has led to decreased TAVR accessibility and utilization among minority groups and those in rural settings 11,12 . The effect of TAVR operator density on utilization of TAVR, and the ramifications of restricting low‐volume operators on the availability of TAVR therapies in rural settings and to racial minorities is an important consideration that requires additional research.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We also found significant variability in the TAVR operator density and mean procedural volume by state‐ these findings are in support of prior studies demonstrating extensive geographic variation in the rates of TAVR utilization among the general population 9,10 . Geographic barriers are a single but important variable in an otherwise complex construct affecting access to TAVR care including socioeconomic status, ethnicity, race, and insurance status, which combined has led to decreased TAVR accessibility and utilization among minority groups and those in rural settings 11,12 . The effect of TAVR operator density on utilization of TAVR, and the ramifications of restricting low‐volume operators on the availability of TAVR therapies in rural settings and to racial minorities is an important consideration that requires additional research.…”
Section: Discussionsupporting
confidence: 84%
“…9,10 Geographic barriers are a single but important variable in an otherwise complex construct affecting access to TAVR care including socioeconomic status, ethnicity, race, and insurance status, which combined has led to decreased TAVR accessibility and utilization among minority groups and those in rural settings. 11,12 The effect of TAVR operator density on utilization of TAVR, and the ramifications of restricting low-volume operators on the availability of TAVR therapies in rural settings and to racial minorities is an important consideration that requires additional research. TAVRs per year preclude operator level analysis, thus summary data was utilized.…”
Section: Per Year)mentioning
confidence: 99%
“…Furthermore, language barriers and a lack of trust in the US health care system, given a long history of discrimination, may also contribute to the findings among certain patient groups. 25 Prior studies 11,12 have demonstrated an urban-rural divide in the availability of TAVR services, with few TAVR centers present in rural areas. However, within major metropolitan areas with existing TAVR programs, in which the local population should have ready geographic access to a hospital capable of TAVR, there was tremendous racial, ethnic, and socioeconomic variation in TAVR rates, which we used as a surrogate for procedure availability.…”
Section: Discussionmentioning
confidence: 99%
“…11 Some of this disparity is explained by geographic factors; most TAVR centers opened in metropolitan areas with existing TAVR centers, and few TAVR centers were initially located in rural areas. 11,12 However, physical proximity may not be sufficient to guarantee access to a procedure. Biases in initial diagnosis, care delivery, referral patterns, social determinants of health (such as the ability to miss work for medical appointments), availability of transportation to subspecialist appointments and testing, language barriers, lack of trust in the health care system, and other structural factors may also represent barriers to accessing high-technology health care for vulnerable populations.…”
mentioning
confidence: 99%
“…Granular data, such as the etiology of ESRD, type or renal replacement therapy, and compliance, were also unavailable. There may be a selection bias by distance and population density as patients who travel to outside states are lost and those who travel longer distances to the hospital may be subject to worse outcomes [ 44 ]. Our Kaplan-Meier curves did not account for patients who died after discharge.…”
Section: Discussionmentioning
confidence: 99%